analisis infeksi luka operasi post sectio caesarea di RSIA Selaras - nadia annisa nurani (Yayasan Pendidikan Medika Indonesia, 2021)
Background: The hospital is responsible for patient safety. The high rate of surgical site infection (SSI) in RSIA Selaras will affect the quality the healthcare services. From January to June 2021, the SSI had been increased in RSIA Selaras. With the intention of that, it needs the research to understand the probability factors of the SSI and the needs to improve the intervention of the infection control team to care the surgical site infection in the hospital. Aims : To acknowledge the risk factors which will affect the SSI in RSIA Selaras Methods : The research method in this study is descriptive using the retrospective approach. Collecting the secondary data from the medical, proceed and proceeding to analyze/ to research with the aim to get quantitative data. The secondary data is the SSI record from January to Mei 2021 in maternity and pediatrics RSIA Selaras. Result : The surgical site infection has been affected by the age factor, which is caused by the organ function particularly the skin changes. As well as the duration of the surgery also affects the SSI, this is caused by the surgical duration of more than 2 hours which will be risked microorganism contamination. Yet the surgical duration of less than 2 hours will not assure the good surgery. According to the criteria of the surgery wounds, its show that the differences characteristic of the surgery wound infections are affected by after surgery care, antibiotic prophylax usage, preoperative intraoperative and postoperative. Conclusion: the surgery site infection could be affected by several factors, particularly the age, surgical duration, and SSI critetria. The role of the infection control teams is necessary actively in the prevention and treatment of the of the SSI